Implementasi 5S dengan Merancang Sistem Informasi Visual pada Gudang di PT Surveyor Indonesia. - Nofirza Nofirza; Khairul Amri (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2016)
PT surveyor Indonesia's warehouse has a function as a storage of operating equipment, which is the placement was not set in the right place, dirty dan there was no visual information as a guide for searching and borrowing an equipment. This research aims to improve the layout of operating equipment at the warehouse used 5S method and make the process of borrowing and returning equipment is easily and quickly. On this research, 5S methods namely: sort (seiri), set in order (seiton), shine (seiso), standardize (siketsu) and sustain (shitsuke) equipped with visual information system design that produces 4 navigation menus. This research results a design of the operation equipment layout with a better organizing and produced a design of visual information, that provide information in the process of borrowing and saving back operation equipment at the warehouse. That information presented in its entirety, from borrower name, equipment availability, the amounts of borrowed and map for the equipment that would borrow in the form of photos.Keywords: 5S, layout, visual information system, warehouse